Transcendence of computer vision syndrome due to prolonged exposure to electronic devices: Trascendencia del síndrome visual informático por exposición prolongada a dispositivos electrónicos - Custodio Sanchez, Klisman Lennon (2021)
Eye health, without a doubt, has been gaining more relevance in recent years due to the promotion of healthy habits in search of caring for our eyes, but the question also arises as to whether we are increasingly exposed to electronic devices with screens, these, can be detrimental to our visual well-being since, due to confinement, the use of these as a work and study tool has increased exponentially.